Admixture of Isubgol husk together with conventionally used agar as gelling agent for Potato and Stevia regeneration (Bangladesh Journal of Scientific and Industrial Research, 2012)
Attempts have been made to find a substitute for agar as gelling agent. The study was conducted on commercially important crop plants like    potato varieties (Diamond and Granola) and Stevia. 'Isubgol', the mucilaginous husk, derived from Plantago ovata was successfully used as a gelling material in tissue culture media. The price of 'Isubgol husk' is cheaper than the conventionally used agar and it had reduced the price of gelling agent approximately by 47.5 % in plant tissue culture media. The use of 'Isubgol husk' along with agar can reduce the cost of gelling agents. The response from media gelled with Isubgol husk in potato and Stevia was similar to that from media solidified with agar. DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11447 Bangladesh J. Sci. Ind. Res. 47(2), 161-166, 2012